Tokyo these days. 1 - Matsumoto, Taiyō, 1967- (Viz signature., 2024)
After 30 years as a manga editor, Kazuo Shiozawa suddenly quits. Although he feels early retirement is the only way to atone for his failures as an editor, the manga world isn't done with him. On his final day as an editor, Shiozawa takes a train he's ridden hundreds of times to impart some last advice to a manga creator whose work he used to edit. Later, he is drawn to return to a bookshop at the request of a junior editor who wants his help dealing with an incorrigible manga creator who used to be edited by Shiozawa and now refuses to work with anyone else. For Shiozawa, Tokyo these days is full of memory and is cocooned in the inescapable bonds among manga creators, their editors, art, and life itself.